(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2025)
Introduction:Suicide is a major public health issue in India and the third leading cause of death among people aged 15–29 years. According to NCRB 2022, India reported 170,924 suicide deaths, showing a 4.2% increase from the previous year and a 27% rise since 2018, with a suicide rate of 12.4 per 100,000 population. Vulnerable groups include young adults, women, students, daily wage earners, and farmers. This review analyzes suicide trends in India from 2018 to 2022, highlighting demographics, causes, and policy implications.Methods:The review followed PRISMA 2020 guidelines. Literature was searched in PubMed, Scopus, Web of Science, Google Scholar, NCRB reports, WHO publications, and government documents. Search terms included “Suicide India,” “Mental Healthcare Act 2017,” “NCRB suicide statistics,” and “National Suicide Prevention Strategy.” Inclusion criteria were NCRB reports and peer-reviewed English-language studies from 2018 to 2022. Data on epidemiology, risk factors, methods, and policies were extracted and synthesized.Results:Suicide mortality rose from 10.2 to 12.4 per 100,000 between 2018 and 2022. Men accounted for nearly three-fourths of deaths. About 67% of suicides occurred among individuals aged 18–45. Major causes included family conflict (31.7%), chronic illness (18.4%), economic distress, and substance abuse. Hanging (58.2%) and pesticide ingestion were the leading methods. Student suicides ( 13,000 annually) and farmer suicides (11,290 in 2022) remain significant challenges. Geographic disparities showed higher burdens in Maharashtra, Tamil Nadu, Madhya Pradesh, Kerala, and Chhattisgarh. Legislative responses included the Mental Healthcare Act, 2017, and the National Suicide Prevention Strategy, 2022, aligned with the WHO “LIVE LIFE” framework. Conclusion:Suicide in India reflects a complex interplay of social, economic, and psychological factors. Preventive efforts must focus on strengthening mental health services, restricting access to means, improving surveillance, and reducing stigma. Forensic medicine contributes critical evidence for surveillance and policy. A multisectoral, evidence-based approach is essential to reverse the rising trend.